Identifikasi Fitosterol dengan Kromatografi Gas –Spektrometer Massa pada Ekstrak Kloroform Biji Buah Atung (Parinarium GlaberimumHassk) Asal Kabupaten Seram Bagian Barat, Maluku - Candra Yulius Tahya; Elen Tiwery; Mega Gracelia Monaten; Tryani K. Junita Lumbantoruan (JC-T (Journal Cis-Trans): Jurnal Kimia dan Terapannya, 2020)
Five main compounds have been identified in the chloroform extract of Atung fruit seeds (Parinarium glaberimum Hassk) which are linoleic acid (8.88%); stearic acid (8.23%); stigmasta-5,22-dien-3-ol,(3β,22E) or stigmasterol (10.37%); stigmast-5-en-3-ol,(3β) or β-sitosterol (19.59%); and stigmast-5-en-3-ol, (3β, 24S) or γ-sitosterol ( 33.74%) through gas chromatography-mass spectroscopy by analyzing the similarity of molecular weight and positive ion mass/charge fragments and based on the comparison of the GC-MS retention time of phytosterols. This study is the first to report the presence of stigmasterol, β-sitosterol and γ-sitosterol in the chloroform extract of Atung fruit seeds (Parinarium glaberimum Hassk). γ -Sitosterol, the epimer of β-sitosterol, has the greatest abundance in the chloroform extract of Atung fruit seeds. Phytosterol compounds namely stigmasterol, β-sitosterol, and γ-sitosterol have been reported to have many benefits such as reducing blood cholesterol levels, antioxidants, anti-diabetic, anti-inflammatory, and anti-cancer.